Continuous Assessment in the Finance Classroom in Time of PostCovid-19 - Latorre Guillem, Miguel Ángel (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2022)
This study addresses the impact on university teaching caused by the Covid-19 pandemic and the lecturer's reflection on the continuous assessment system in view of the return to face-to-face or blended learning in the classroom. The results obtained show that through the new assessment criteria, students are more participative as they are more familiar with the specific competences of the subject. Moreover, the methodological changes applied provide the evaluation process in the finance classroom with a notable improvement for its adaptation to the professional environment.